A major food transfer program in Bangladesh fell short during the COVID-19 pandemic - Bin Khaled, Muhammad Nahian; Raghunathan, Kalyani; Rashid, Shahidur; Dearlove, Honor; Chowdhury, Shyamal (International Food Policy Research Institute, 2022)
Public food transfer programs serve as an important safety net for those facing hunger and food insecurity in both low- and high-income countries around the world. During the COVID-19 pandemic, these programs have become even more crucial, as food insecurity and poverty rates have soared. But lockdowns and other public health restrictions can also disrupt food distribution operations and thus limit their effectiveness.